Ethnopedagogics in the field of humanities - Mariyat Aslanovna Tlevtsezheva (Вестник Майкопского государственного технологического университета)
Rapid socio-cultural changes taking place in our country entail an inalienable modernization of all spheres of the material and spiritual life of society. This process has not bypassed the traditional education system. Every day the new concept of higher education makes more and more new requirements for the system of training specialists. A kind of «swing» from technical to humanitarian education is a rather old phenomenon, and today, apparently, the creators of artificial intelligence receive a clear priority in the development of educational programs for training specialists of any direction. «New challenges» of modern society entail new problems, one of them, in our opinion, is changes in the world of values. Therefore, the upbringing of deep respect for the culture of other peoples, the formation of the value-semantic component of the life of the young generation is the most relevant direction in education, which is adequately handled by one of the subsystems of Pedagogics - Ethnopedagogics. The aim of the study is to analyze Ethnopedagogics as a humanitarian resource of the education system. The multidimensional nature of the problem has made it possible to use the methods of interdisciplinary synthesis to form an interconnected complex of ideas about Ethnopedagogics as an integral and diverse scientific knowledge.